Corporate Nationality and Capital Structure Decisions - Evidence from India - Ms. Aparna Bhatia; Ms. Pooja Kumari (Ramanujan International Journal of Business and Research, 2021)
This paper examines the Capital Structure of companies classified based on nationality over two-time phases as 2008-09 to 2012-13 and 2013-14 to 2017-18 covering ten years. For each category of companies, the mean of three gearing ratios i.e., Total debt to Net worth ratio, Long term debt to Net worth ratio and Short term debt to Net worth ratio is assessed. The analysis is based on a randomized sample of 206 companies obtained from BT-500 (December, 2017) which are subcategorized on the basis of nationality as Indian Domestic Companies, Indian MNCs operating abroad and Foreign MNCs operating in India. The findings reveal that Domestic Indian companies are more inclined towards debt relative to Indian MNCs and Foreign MNCs over both the time phases. This signifies the importance of the nationality factor which must be contemplated while planning Capital Structure. Statistically significant differences in total and long-term debt ratios of Domestic Indian Companies and Indian MNCs between Phase I and Phase II highlight the significance of the time factor which should also be kept in mind before taking leverage decisions. Overall, the paper suggests the corporations to have beady eyes on the institutional environment of geographical territories in which they operate as well as the time variations before planning their debt structure. The disparities in the debt ratios across nationality and time warrant an empirical investigation of the causes behind them, so examining the determinants of Capital Structure of DCs and MNCs would be an interesting area of research in the future.